Emotional prosody effects on verbal memory in older and younger adults. Issue 4 (4th July 2017) - Fairfield, Beth; Di Domenico, Alberto; Serricchio, Sonia; Borella, Erika; Mammarella, Nicola
ABSTRACT: Prosody, or the way things are said, can modify the meaning of utterances making qualitatively different affective prosodies useful for understanding how auditory affective information is processed and remembered. In this study, we collected behavioral data from 225 younger ( M age = 20.8 years, SD  = 2.5 years; 119 males) and 225 older adults ( M age = 71.6 years, SD  = 6.5 years; 119 males) in order to examine age differences in emotional prosody effects on verbal memory. Participants were randomly divided into three subgroups according to different prosody listening conditions (positive, negative, and neutral) and prosody effects on a yes–no recognition memory task were investigated. The results showed how older adults who listened to the story read with a neutral prosody remembered more words than those who listened to the same story with a positive or negative prosody. Younger adults showed no valence effects. Our findings highlighted an age and affective prosody interaction that affects remembering in older adults alone.